Zinc Deficiency, Plasma Fatty Acid Profile and Desaturase Activities in Hemodialysis Patients: Is Supplementation Necessary? - Takic, Marija; Zekovic, Milica; Terzic, Brankica; Stojsavljevic, Aleksandar; Mijuskovic, Mirjana; Radjen, Slavica; Ristic-Medic, Danijela (Frontiers in Nutrition, 2021)
Background: The relationships between serum zinc (Zn) concentrations, nutritional status and clinical outcomes remain unclear among hemodialysis (HD) patients. There is limited information about the association of plasma phospholipid fatty acid (PUFA) profile and Zn status in this patient population. Objective: To examine the relationships between dietary and serum levels of Zn and Cu/Zn ratio and to explore associations of these micronutrients with PUFA profile and estimated desaturase and elongase enzyme activities in serum phospholipids among HD patients. Methods: This study included 40 adult patients undergoing hemodialysis treatment. Repeated 24-h recalls were applied for dietary intake assessment. Serum concentration of Zn and Cu were determined using inductively coupled plasma mass spectrometry and fatty acid composition by gas-liquid chromatography. Desaturase and elongase activities were calculated from product-precursor fatty acid ratios. Results: Inadequate dietary Zn intake was found in 55% of HD patients. They all had serum Zn concentration below the reference value of 60 µg/dL (mean 38.8±7.72 μg/dL). There was no correlation between Zn serum status and Zn intake estimates. Serum Cu/Zn ratio was high, (2.76±0.68), directly and significantly associated with HD period, CRP, BMI, VFA, and inversely with KtV, albumin, iron, and iPTH. The n-6/n-3 ratio in plasma phospholipids was elevated (12.25±3.45) and patients with inadequate Zn intake had lower n-3 PUFA levels compared to those with adequate intake. Serum Zn concentrations were inversely correlated with linoleic/dihomo-γ-linolenic acid ratio (LA/DGLA), related to D6-desaturase activity (p=0.033) and directly with DGLA relative abundances (p=0.024). Cu status was inversely associated with EPA level (p=0.03) and estimates of elongase activity (p=0.001). Furthermore, positive relationship was found between the Cu/Zn ratio and determined elongase value (p=0.01). Conclusion: Due to high prevalence of Zn deficiency and inadequate EPA+DHA status, our study underpins the need for individually tailored dietary regimes in HD patients. The results obtained indicate that assessment of Zn status should be a standard parameter of nutritional status screening in HD patients while emphasizing the importance of Cu/Zn determination. Although further research is warranted, we hypothesize that zinc and EPA+DHA supplementation could induce even more favorable change in fatty acids profiles than EPA+DHA supplementation alone.